Long-term changes in numbers and distribution of wintering waterbirds in the Czech Republic, 1966 - 2008 - Poláková, Simona (Jihočeská univerzita, 2012)
This paper assessed long-term trends in the numbers and distribution of the 26 most abundant wintering waterbird species in the Czech Republic. Data were based on International Waterbird Census data, that started in our country in 1966. Climatic variables and all-european trends were taken in account.
Long-term changes in numbers and distribution of wintering waterbirds in the Czech Republic, 1966 - 2008
Keywords: waterbirds; long-time trends in numbers and distribution; TRIM; waterbirds; long-time trends in numbers and distribution; TRIM